1986
DOI: 10.1103/physreva.34.493
|View full text |Cite
|
Sign up to set email alerts
|

Far-infrared spectroscopy on oriented films of dry and hydrated DNA

Abstract: Far-infrared measurements, between 3 and 450 cm ', of absorption spectra of highly oriented films of Li-DNA and Na-DNA in the temperature range 5 -300 K are reported. Five lowfrequency infrared-active vibrational modes are observed. The lowest infrared-active mode at 45 cm ' for Li-DNA and 41 cm ' for Na-DNA, as observed for the first time, is found to soften upon sample hydration. Studies of the hydration-induced absorption at the low-frequency end of the spectrum also show a pronounced absorption band at abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(61 citation statements)
references
References 29 publications
3
58
0
Order By: Relevance
“…Using low-power radiation sources it is simply impossible to penetrate thick layers of water. As a result, studies have been mainly restricted to (bio)molecules embedded in polyethylene, which is transparent in the terahertz region (33), hydrated films of biomolecules (34), and only a few solvents (mainly water and methanol) (35,36). Moreover, to be sure that the surface layers do not influence the results of the measurements, it is important that we probe a sufficiently large volume of the probe.…”
Section: Resultsmentioning
confidence: 99%
“…Using low-power radiation sources it is simply impossible to penetrate thick layers of water. As a result, studies have been mainly restricted to (bio)molecules embedded in polyethylene, which is transparent in the terahertz region (33), hydrated films of biomolecules (34), and only a few solvents (mainly water and methanol) (35,36). Moreover, to be sure that the surface layers do not influence the results of the measurements, it is important that we probe a sufficiently large volume of the probe.…”
Section: Resultsmentioning
confidence: 99%
“…DNA IR absorption measurements [9,10] coupled with lattice dynamic analysis [11] demonstrated that DNA low-frequency vibrations produce characteristic absorption bands in the far-IR region (between 40 and 300 cm )1 ) which are sensitive both to DNA composition and to environment [10]. Our own IR absorption measurements of salmon DNA [12] revealed that in the long-wave spectrum region (from 2 to 250 cm )1 ) the resonance peaks have a very high density.…”
Section: Introductionmentioning
confidence: 98%
“…Far-infrared absorption spectroscopy in the terahertz frequency range provides another access to the low-frequency vibrational excitations of DNA. Besides Fourier-transform spectroscopy [9][10][11] and absorption spectroscopy using tunable terahertz light sources, 12,13 time-domain terahertz spectroscopy became available recently to study optical properties of biomolecules and DNA. [14][15][16][17] In this letter, we use a recently developed terahertz spectrometer based on high-speed asynchronous optical sampling ͑ASOPS͒ to measure the terahertz transmission characteristics of highly oriented wet-spun DNA films.…”
Section: -4mentioning
confidence: 99%
“…24,25 The increase of the extinction coefficient in this frequency range has been calculated and differences concerning the light polarization have been predicted in a simple model. 9 However, difficulties in the observation of a polarization dependence of the terahertz absorption was reported. Our data clearly represent distinct differences in the terahertz absorption for the two polarization orientations.…”
Section: -4mentioning
confidence: 99%